(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2020)
A census of Laguncularia racemosa var. glabriflora was carried out in the Gulf of Guayaquil to assess the status of the populations. During December 2020 and January 2021, 10 rectangularshaped plots were established, each with an area of 50 x 20 m (1,000 m2), covering a total area of 1 hectarea (10,000 m2) in the provinces of Guayas and El Oro, in the coast of Ecuador. Laguncularia racemosa var. glabriflora predominantly inhabits riparian mangroves and muddy (mostly silt) soils with a loose texture, and interstitial salinity from 5 to 38 UPS, the highest population density was recorded in localities that have between 20 to 35 UPS. The recorded populations have a low structural development, corresponding to 56% in the latizal diameter category (5-9.9 cm DBH). The two varieties of L. racemosa are markedly sympatric in the Gulf of Guayaquil. In 80% of the surveyed plots they bloom and fructify simultaneously, however, evidence of morphological variability or hybridization among both varieties has not been found in the field neither in herbarium. These results suggest that biological compatibility would not be achieved among both varieties and that consequently, a review of its taxonomic status based on molecular studies is recommended.